Precision medicine and lymphoma. Issue 4 (July 2018) - Heward, James A.; Kumar, Emil A.; Korfi, Koorosh; Okosun, Jessica; Fitzgibbon, Jude
Abstract : Purpose of review: The treatment of the germinal center lymphomas, diffuse large B cell (DLBCL) and follicular lymphoma, has changed little beyond the introduction of immunochemotherapies. However, there exists a substantial group of patients within both diseases for which improvements in care will involve appropriate tailoring of treatment. Recent findings: DLBCL consists of two major subtypes with striking differences in their clinical outcomes paralleling their underlying genetic heterogeneity. Recent studies have seen advances in the stratification of germinal center lymphomas, through comprehensive profiling of 1001 DLBCLs alongside refinements in the identification of high-risk follicular lymphoma patients using m7-FLIPI and 23G models. A new wave of novel therapeutic agents is now undergoing clinical trials for germinal center lymphomas, with BCR and EZH2 inhibitors demonstrating preferential benefit in subgroups of patients. The emergence of cell-free DNA has raised the possibility of dynamic disease monitoring to potentially mitigate the complexity of spatial and temporal heterogeneity, whilst predicting tumor evolution in real time. Summary: Altogether knowledge of the genomic landscape of germinal center lymphomas is offering welcome opportunities in patient risk stratification and therapeutics. The challenge ahead is to establish how best to combine upfront or dynamic prognostication with precision therapies, while retaining practicality in clinical trials and the real-world setting.